Non-use of community health-care services – an exploratory cross-sectional study among family care-givers for older, home-dwelling persons with dementia - Moholt, Jill-Marit; Friborg, Oddgeir; Henriksen, Nils Oddbjørn; Hamran, Torunn; Blix, Bodil Hansen (Ageing and Society, 2020)
Community health-care services for older, home-dwelling persons with dementia tend to be underutilised. Family care-givers provide substantial care, and they often arrange for and co-ordinate health-care services on behalf of persons with dementia. The aim of this study was to examine family care-givers’ knowledge of unused services and their self-reported reasons for non-use of such services. We gathered cross-sectional survey data from 430 family care-givers of older persons with dementia in Northern Norway. Multinomial logistic regression analysis was used to identify predictors of family care-givers’ knowledge of unused services. An open-ended question regarding reasons for non-use of services was analysed by thematic text analysis. Characteristics of family care-givers (e.g. education level) and factors related to the care-giving circumstances (e.g. negative impact of care-giving) predicted family care-givers’ knowledge of unused services. Reasons for non-use of services were multifaceted and complex, and were related to attributes of the person with dementia and/or the family care-giver (e.g. reluctance to use services) and/or the health-care services (e.g. low quality). Although services were unused, several family care-givers indicated substantial needs for the services. Strategies aimed at addressing the non-use of services should emphasise individuals’ and families’ needs and the adaptation of information about available services and their benefits for both care recipients and family care-givers. A relationship-centred care approach is thus recommended in dementia care.